Risk Mitigation from a Public Service Perspective - Subhan Ilham Thareq (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This article seeks to explain disaster risk mitigation from a public service. The variety of disasters that occur and have the potential in Indonesia requires risk mitigation that public services can run normally. Literature studies conducted by the author through various research journal references related to public service risk mitigation are represented in explaining disaster risk mitigation in the perspective of public service. The findings show that risk mitigation can shape public service providers in facing various risks of natural and non-natural disasters through an understanding built between all stakeholders. The dimensions of compliance, deliberation and collaboration, accountability and transparency, and the use of technology are aspects of risk mitigation to optimize public service.